GENDING NYAPA MANDA TENGAHING DALU KETIKA UPACARA DALEM PINGIT DESA ADAT KINTAMANI SEBAGAI MEDIA PELESTARIAN BAHASA BALI - Dewi, Ni Luh Rista (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Kintamani Traditional Village as a Bali Mula Village has a unique culture, one of which is in the form of literature, namely Gending Nyapa Manda Tengahing Dalu which is classified as an oral tradition. This gending is sung once every year as an accompaniment to the Dewa Yadnya ceremony. This gending can also be used as a means of maintaining the Balinese language, one way is to learn the language in the gending. Therefore, the existence of Gending Nyapa Manda Tengahing Dalu is still maintained today amidst the progress of the times. This indicates that there is a teaching method or process that is used to preserve it. In this research, there are three problem formulations that briefly address the issue of how is the existence, meaning and procedure for preserving the Gending Nyapa Manda Tengahing Dalu Ri Kala Karya Dalem Pingit, Kintamani Traditional Village? This research aims to describe the existence, meaning and procedures for preserving the Gending Nyapa Manda Tengahing Dalu Ri Kala Karya Dalem Pingit, Kintamani Traditional Village. The theories used are structuralism theory, semiotic theory, and functionalism theory. The approach used is qualitative with an ex post facto type of research. Data was obtained using data collection techniques in the form of observation, interviews, documentation and literature study. The results of this research are the existence of the Nyapa Manda Tengahing Dalu gending during the Dalem Pingit Ceremony of the Kintamani Traditional Village, which consists of the history of the gending, the lyrics of the gending, the complementary infrastructure for the gending, the place and time of the gending. The meaning content in the Nyapa Manda Tengahing Dalu gending is; (1) religious meaning, (2) social meaning, (3) meaning of cultural preservation, (4) meaning as a means of preserving the Balinese language, (5) meaning of entertainment. The procedure for preserving the Nyapa Manda Tengahing Dalu gending is through teaching methods, namely (1) direct method, (2) reading method, (3) audiolingual method, (4) imitation method.